Identification of Key Residues in Subgroup A Avian Leukosis Virus Envelope Determining Receptor Binding Affinity and Infectivity of Cells Expressing Chicken or Quail Tva Receptor - Holmen, Sheri L. (American Society for Microbiology, 2001)
To better understand retroviral entry, we have characterized the interactions between subgroup A avian leukosis virus [ALV(A)] envelope glycoproteins and Tva, the receptor for ALV(A), that result in receptor interference. We have recently shown that soluble forms of the chicken and quail Tva receptor (sTva), expressed from genes delivered by retroviral vectors, block ALV(A) infection of cultured chicken cells (∼200-fold antiviral effect) and chickens (>98% of the birds were not infected). We hypothesized that inhibition of viral replication by sTva would select virus variants with mutations in the surface glycoprotein (SU) that altered the binding affinity of the subgroup A SU for the sTva protein and/or altered the normal receptor usage of the virus. Virus propagation in the presence of quail sTva-mIgG, the quail Tva extracellular region fused to the constant region of the mouse immunoglobulin G (IgG) protein, identified viruses with three mutations in the subgroup A hr1 region of SU, E149K, Y142N, and Y142N/E149K. These mutations reduced the binding affinity of the subgroup A envelope glycoproteins for quail sTva-mIgG (32-, 324-, and 4,739-fold, respectively) but did not alter their binding affinity for chicken sTva-mIgG. The ALV(A) mutants efficiently infected cells expressing the chicken Tva receptor but were 2-fold (E149K), 10-fold (Y142N), and 600-fold (Y142N/E149K) less efficient at infecting cells expressing the quail Tva receptor. These mutations identify key determinants of the interaction between the ALV(A) glycoproteins and the Tva receptor. We also conclude from these results that, at least for the wild-type and variant ALV(A)s tested, the receptor binding affinity was directly related to infection efficiency.